Update on the development of an app (adaptation of iMammalia) for early reporting of wild boar carcasses by a warning system. Issue 2 (21st February 2022) - ; Blanco‐Aguiar, JA; Smith, GC; Vicente, J
Abstract: Citizen science (CS) has been increasingly used in wildlife disease surveillance since it can facilitate the detection and recovery of carcasses of target species used as sentinels of infection. This report updates on the improvement of an app adapted from iMammalia (MammalNet project) for early reporting carcasses of wild boar with a warning system. This app has a great potential for improving wildlife disease surveillance (carcass reporting), such as for ASF. The app has been expanded in the context of ENETWILD project during the second part of 2021 to several countries in their respective languages: Italy, Greece, Serbia, Montenegro, Kosovo, Bosnia‐Herzegovina, North Macedonia, Albania, and the latest to incorporate, Portugal. The ENETWILD project has generated alliance with FAO to promote the use of iMammalia in the Balkans to collect data in gap areas about the distribution of wild boar, to document the presence of carcasses of dead animals. The technical improvements that have been made to meet the needs of iMammalia to report the presence of wild boar carcasses correspond to the possibility of recording different parameters, such as sex, age, whether the dead animal has been hunted or not, or the degree of decomposition observed. The possibility of generating warnings to notify these records in real time to wildlife and/or sanitary services will be implemented in 2022. To date, iMammalia collected 14, 393 mammal observations all over Europe, 797 of which corresponds to wild boar. A total of 1, 270 observations correspond to animals found dead (5.53%), 30 out of which are wild boar, which, in some cases, were later diagnosed as ASF positive (e.g. in Serbia). We finally summarize the next step of ENETWILD in relation to iMammalia promotion, including an online workshop to provide an overview of disease surveillance systems in Europe, and to propose changes, including the promotion of CS.